2014
DOI: 10.1210/jc.2013-3351
|View full text |Cite
|
Sign up to set email alerts
|

Indoleamine 2,3-Dioxygenase 1 (IDO1) Is Up-Regulated in Thyroid Carcinoma and Drives the Development of an Immunosuppressant Tumor Microenvironment

Abstract: For the first time, this study demonstrates a pivotal role of IDO1 in the suppression of lymphocyte function in thyroid carcinoma microenvironment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
62
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 35 publications
7
62
0
Order By: Relevance
“…However, when an inhibitor of the the indoleamine 2,3-dioxygenase (IDO) enzyme (1-methyltriptophan) was given together with the RET peptide (Zeng et al 2009), effective anti-tumor immunity was elicited. Interestingly, IDO expression can be increased by activated RET in a STAT1-dependent manner (Moretti et al 2014). These data confirm that RET induces the expression of immunosuppressive molecules and that anti-cancer immunity can be elicited only when these molecules are blocked.…”
Section: Ret and Cancer Immunotherapy In Men2supporting
confidence: 59%
“…However, when an inhibitor of the the indoleamine 2,3-dioxygenase (IDO) enzyme (1-methyltriptophan) was given together with the RET peptide (Zeng et al 2009), effective anti-tumor immunity was elicited. Interestingly, IDO expression can be increased by activated RET in a STAT1-dependent manner (Moretti et al 2014). These data confirm that RET induces the expression of immunosuppressive molecules and that anti-cancer immunity can be elicited only when these molecules are blocked.…”
Section: Ret and Cancer Immunotherapy In Men2supporting
confidence: 59%
“…Recently, studies have shown that the BRAF V600E protein mutation is associated with immunosuppressive mechanisms in PTC, such as indoleamine 2,3-dioxygenase 1 (IDO) (23), human leukocyte antigen G (HLA-G) (24), and programmed death ligand 1 (PD-L1) expression (25). Studies of TIL in other cancer types have shown that specific patterns predict cancer behavior, such as the correlation between a low CD8 + effector T cell to FoxP3 + suppressor T cell ratio with greater tumor aggressiveness and worse patient outcomes (17,(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Cultured mouse peritoneal Mac1 + macrophages (E) and splenic CD11c + dendritic cells (F) strongly expressed IDO upon stimulation with interferon gamma. (30,31), a neoplasia long known to be associated with a prominent lymphocytic infiltration (32). Several drugs are therefore being developed to decrease the levels of IDO (and thus increase the extracellular concentration of tryptophan) as a way to boost the activity of tumor-specific effector T cells (33).…”
Section: Discussionmentioning
confidence: 99%